Local adaptation of switchgrass drives trait relations to yield and differential responses to climate and soil environments. Issue 5 (16th March 2023) - Ricketts, Michael P.; Heckman, Robert W.; Fay, Philip A.; Matamala, Roser; Jastrow, Julie D.; Fritschi, Felix B.; Bonnette, Jason; Juenger, Thomas E.
Abstract: Switchgrass, a potential biofuel crop, is a genetically diverse species with phenotypic plasticity enabling it to grow in a range of environments. Two primary divergent ecotypes, uplands and lowlands, exhibit trait combinations representative of acquisitive and conservative growth allocation strategies, respectively. Whether these ecotypes respond differently to various types of environmental drivers remains unclear but is crucial to understanding how switchgrass varieties will respond to climate change. We grew two upland, two lowland, and two intermediate/hybrid cultivars of switchgrass at three sites along a latitudinal gradient in the central United States. Over a 4‐year period, we measured plant functional traits and biomass yields and evaluated genotype‐by‐environment (G × E) interaction effects by analyzing switchgrass responses to soil and climate variables. We found substantial evidence of G × E interactions on biomass yield, primarily due to deviations in the response of the southern lowland cultivar Alamo, which produced more biomass in hotter and drier environments relative to other cultivars. While lowland cultivars had the highest potential for yield, their yields were more variable year‐to‐year compared to other cultivars, suggesting greater sensitivity to environmental perturbations. Models comparing soil and climate principal components as explanatory variables revealed soil properties, especially nutrients, to be most effective at predicting switchgrass biomass yield. Also, positive correlations between biomass yield and conservative plant traits, such as high stem mass and tiller height,   became stronger at lower latitudes where the climate is hotter and drier, regardless of ecotype. Lowland cultivars, however, showed a greater predisposition to exhibit these conservative traits. These results suggest switchgrass trait allocation trade‐offs that prioritize aboveground biomass production are more tightly associated in hot, dry environments and that lowland cultivars may exhibit a more specialized strategy relative to other cultivars. Altogether, this research provides essential knowledge for improving the viability of switchgrass as a biofuel crop. Abstract : Switchgrass is a biofuel crop that could help reduce reliance on fossil fuels. To understand how switchgrass production might respond to climate change, we planted six cultivars in replicate 6m x 6m plots at three sites across its natural latitudinal range and studied the effects of genotype‐by‐environment (G × E) interactions on yield. Soil and climate environments were analyzed independently and plant trait contributions to yield were examined. We found that lowland ecotypes originating from hot, dry climates drive G × E interactions and have greater variability in yield under changing environments. This research will help inform the agricultural production of switchgrass in the coming century.